What causes patients to trust medical professionals? Insights from mothers in Juba - Rachel Ayrton; Christine Mori Lado; Edward Eremugo Luka (Health and Social Sciences Research Institute - South Sudan (HSSRI-SS), 2017)
Trust in medical professionals is an important aspect of demand for health care in South Sudan, without which many patients may never attempt to access clinics and hospitals. This qualitative research study used in-depth biographical interviews to explore family health histories according to the experiences of South Sudanese mothers in Juba. The resulting data demonstrates that trust in medical professionals is conditional on patients' particular experiences. Participants acknowledged the resource constraints that medical professionals work under, and called on decision-makers to prioritise health services as an indicator of peace. Nevertheless, health care workers can take practical steps to build trust through their day-to-day interactions with patients. In addition to medical competence, participants valued a respectful, attentive and supportive quality of care, and working practices that ensured accountability in the way this care was delivered.